2016
DOI: 10.1016/j.ijdevneu.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular space diffusion analysis in the infant and adult rat striatum using magnetic resonance imaging

Abstract: The extracellular space (ECS) in the brain provides an extrasynaptic transfer channel among neurons, axons and glial cells. It is particularly important in the early stage after birth, when angiogenesis is not yet complete and the ECS may provide the main pathway for metabolite transport. However, the characteristics of extracellular transport remain unclear. In this study, a novel magnetic resonance imaging (MRI) method was used to perform real-time visualization and quantification of diffusion in the brain E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…However, the magnitude, locus, and proportions of the brain ISS are not static. Significant transformations ensue in ISS during the development of the brain due to events such as neurogenesis, neuronal migration and differentiation, expansion of dendritic tree, synaptogenesis, gliogenesis, synaptic stripping by microglia, and myelination [1,[5][6][7][8][9][10]. The geometry of the brain ISS also undergoes modification in aging due to the loss of synapses, neurons, dendritic regression, changes in morphology and numbers of glia, senoinflammation, and deposition of amyloid plaques [11][12][13][14][15].…”
Section: The Geometry Of the Brain Issmentioning
confidence: 99%
“…However, the magnitude, locus, and proportions of the brain ISS are not static. Significant transformations ensue in ISS during the development of the brain due to events such as neurogenesis, neuronal migration and differentiation, expansion of dendritic tree, synaptogenesis, gliogenesis, synaptic stripping by microglia, and myelination [1,[5][6][7][8][9][10]. The geometry of the brain ISS also undergoes modification in aging due to the loss of synapses, neurons, dendritic regression, changes in morphology and numbers of glia, senoinflammation, and deposition of amyloid plaques [11][12][13][14][15].…”
Section: The Geometry Of the Brain Issmentioning
confidence: 99%
“…However, at present, the functional mechanisms, hydromechanical characteristics, and components of ISF in the deep brain are not clear. Much research has focused on clarifying the properties and regulatory mechanisms of ISF flow in the deep brain [ 12 - 15 ], and it has been shown that external stimulation can affect ISF flow in the thalamus (Tha) [ 16 ]. AQP4, widely distributed on the foot processes of astrocytes, plays a critical role in interstitial flow [ 17 ].…”
mentioning
confidence: 99%
“…The same team of researchers recently found that the cerebral interstitial fluid drainage was partitioned and the new division was completely different from any previous regionalization. [20][21][22] This finding was helpful for exploring the mechanism underlying SDD.…”
Section: Parameters As a New Diagnostic Methods In Therapeutic Evaluatmentioning
confidence: 96%
“…After TTC staining, the authors found that the infarct volume in the citicoline group was markedly smaller than that in the pMCAO group, which indicated the effectiveness of SDD. The same team of researchers recently found that the cerebral interstitial fluid drainage was partitioned and the new division was completely different from any previous regionalization . This finding was helpful for exploring the mechanism underlying SDD.…”
mentioning
confidence: 92%